Activity-Tuning of Supported Co–Ni Nanocatalysts via Composition and Morphology for Hydrogen Storage in MgH2 - Ding, Xiaoli; Ding, Hongfei; Song, Yun; Xiang, Cuili; Li, Yongtao; Zhang, Qingan (Frontiers in Chemistry, 2020)
Developing cheap metal nanocatalysts with controllable catalytic activity is one of the critical challenges for improving hydrogen storage in magnesium (Mg). Here, it is shown that the activity of graphene-anchored Co–Ni nanocatalysts can be regulated effectively by tuning their composition and morphology, which results in significantly improved hydrogen storage in Mg. The catalytic activity of supported Co–Ni nanocatalysts is demonstrated to be highly dependent on their morphology and composition. When Ni was partly substituted by Co, the shape of these nanocatalysts was changed from spherical to plate-like, thus corresponding to a decrease in activity. These alterations intrinsically result in enhanced hydrogen storage properties of MgH2, i.e., not only does it exhibit a decreased peak desorption temperature but also a positive change in the initial activation for sorption. The results obtained provide a deep understanding of the tuning of catalytic activity via composition and morphology and further provide insights into improving hydrogen storage in Mg-based materials.